DIVERSITAS GENETIK DAN HAPLOGROUP KAMBING GEMBRONG BERSTATUS KRITIS DI KABUPATEN KARANGASEM, BALI (Genetic Diversity and Haplogroup of Endangered Gembrong Goat In Karangasem, Bali) - M. Syamsul Arifin Zein; Sri Sulandari; Jakaria Jakaria; I Made Londra; Suprio Guntoro; Ida Bagus Gaga Partama (Jurnal Kedokteran Hewan, 2016)
This study was conducted to evaluate the genetic diversity and phylogeny of Gembrong goat. For this purpose, 21 goats from endangered breed in Karangasem Bali were used. Molecular analysis of genetic diversity and phylogeography used hypervariable segment 1 of mitochondrial DNA control region. The result showed that genetic variability of Gembrong goat was homogeneous with only one different sites, namely the substitution pyrimidines of C ↔ T (transitional). Phylogeny analysis results showed maternal origin of Gembrong goat is lineage (subhaplogroup) B1 with frequency of 100%. Haplogroup B were known has been domesticated from wild goat in western Asia, then headed to south Asia and infiltrated to southeast Asia, including Gembrong goat in Bali, Indonesia. As a conclusion, genetic diversity of Gembrong goat from remaining population in Karangasem very low and originate from lineages/haplogroup B1 with a frequency of 100%.